Jurnal BUSINESS & ENTREPRENEURSHIP: factors affecting brand choice of the consumers on sports drinks - Galih andihka, Lilik noor yuliati; kirbrandoko (SB-IPB, 2016)
pertumbuhan fitnes center di Indonesia menjadi peluang yang sangat bagus dalam pertumbuhan industri sport drink